2002
DOI: 10.1046/j.1365-8711.2002.05520.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between horizontal flow velocity and cell size for supergranulation using SOHO Dopplergrams

Abstract: A study of 90 supergranular cells obtained from SOHO Dopplergrams was undertaken in order to investigate a possible relation between the sizes and peak horizontal velocities of the cells. For the sample obtained, the two parameters are found to be correlated with a relation: horizontal velocity ∝(size)1/3. This is in agreement with the Kolmogorov theory of turbulence as applied to large‐scale solar convection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
3

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 13 publications
5
24
3
Order By: Relevance
“…Hagenaar et al (1997) found a peak around 12−13 Mm, which is very similar. The maximal extent of this distribution is also close to that of Krishan et al (2002), who used the linear size L = πR, as it covers a similar range of sizes, but our cell sample is much larger. Figure 1 shows for comparison the distributions for no smoothing and for a large smoothing.…”
Section: Supergranule Cell Determinationsupporting
confidence: 77%
See 2 more Smart Citations
“…Hagenaar et al (1997) found a peak around 12−13 Mm, which is very similar. The maximal extent of this distribution is also close to that of Krishan et al (2002), who used the linear size L = πR, as it covers a similar range of sizes, but our cell sample is much larger. Figure 1 shows for comparison the distributions for no smoothing and for a large smoothing.…”
Section: Supergranule Cell Determinationsupporting
confidence: 77%
“…Most studies of the intensity variation accross supergranules found an enhancement at the boundary due to the presence of the network (Beckers 1968;Frazier 1970;Foukal & Fowler 1984;Lin & Kuhn 1992) but recently a decrease of the intensity from the center to the boundary of supergranules has been observed (Rast 2003a;Meunier et al 2006a). Following another approach, Krishan et al (2002) studied the variation of maximum velocities in supergranule cells as a function of their size. They found a slope on a log-log scale of 1/3 surprisingly compatible with an interpretation of supergranulation as a turbulent feature in the Kolmogorov model of turbulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, a linear fit seems reasonable. This result substantially disagrees with the findings of Krishan et al (2002) which found a weak power law with index 0.34, and interpreted this in terms of the solar convective motions obeying the Kolmogorov hypothesis for a turbulent medium. The main reason for this is probably due to bias in their subjective selection method where a small number of unusually large cells were picked by eye.…”
Section: Cell Internal Speedscontrasting
confidence: 98%
“…Following the analysis of and Krishan et al (2002), we looked for a power-law relation between the cell size and internal speeds. For this we selected cells that could be tracked with consistent areas for at least three hours (see Section 4.3), to be certain that the cells were well defined.…”
Section: Cell Internal Speedsmentioning
confidence: 99%